2021
DOI: 10.1186/s12935-021-01915-x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and validation of a prognostic signature for lung adenocarcinoma based on metabolism‐related genes

Abstract: Background Given that dysregulated metabolism has been recently identified as a hallmark of cancer biology, this study aims to establish and validate a prognostic signature of lung adenocarcinoma (LUAD) based on metabolism-related genes (MRGs). Methods The gene sequencing data of LUAD samples with clinical information and the metabolism-related gene set were obtained from The Cancer Genome Atlas (TCGA) and Molecular Signatures Database (MSigDB), re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 52 publications
2
31
0
Order By: Relevance
“…TYMS has been proved to be the downstream target gene of miR-375-3p, which enhances the chemosensitivity of CRC cells to 5-fluorouracil (5-Fu) [ 42 ]. Also, when it comes to LUAD, TYMS has been sorted as one of the differentially expressed metabolism-related genes (MRGs), which provides the evidence on the possible role of TYMS in LUAD [ 43 ]. However, its interaction with miR-140-3p, to be precisely, remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…TYMS has been proved to be the downstream target gene of miR-375-3p, which enhances the chemosensitivity of CRC cells to 5-fluorouracil (5-Fu) [ 42 ]. Also, when it comes to LUAD, TYMS has been sorted as one of the differentially expressed metabolism-related genes (MRGs), which provides the evidence on the possible role of TYMS in LUAD [ 43 ]. However, its interaction with miR-140-3p, to be precisely, remained poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Least absolute shrinkage and selection operator (LASSO) analysis and multivariate Cox regression analysis were applied to construct a prognostic signature. The risk score formula of the prognostic signature was as follows: Risk score = coef * Exp (geneA) + coef * Exp (geneB) + coefi * Expi (genei) [ 33 , 34 ]. The 90 patients were divided into high- and low-risk groups according to the median risk score (1.244).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, it is widely accepted that the metabolic mechanisms play crucial roles in the initiation and development of cancer. Studies have shown that metabolism-related genes are involved in lung cancer [ 14 ], gastric cancer [ 15 ], and liver cancer [ 16 ]. However, only a few investigations have focused extensively on the association of metabolic genes with OSCC.…”
Section: Introductionmentioning
confidence: 99%